Effect of sarcopenia, osteoporosis, and osteosarcopenia on spine fracture in American adults with prediabetes - Liu, Yufang; Chai, Sanbao; Zhang, Xiaomei (Frontiers in Endocrinology, 2023)
Objective This study aimed to investigate the association between sarcopenia, osteoporosis and prediabetes, and the effect of sarcopenia, osteoporosis and osteosarcopenia on spine fracture in patients with prediabetes. Methods We collected and analyzed data from the U.S. National Health and Nutrition Examination Surveys (NHANES) during the period from 2009 to 2018. Bone mineral density (BMD) and skeletal muscle mass index (SMI) were measured with dual-energy X-ray absorptiometry (DXA). Diagnosis of spine fracture was based on DXA and history. Results People with prediabetes were more likely to develop sarcopenia than normal glucose tolerance (NGT) subjects (OR 1.33, 95% CI 1.07–1.66), while there was no significant increase of osteoporosis in prediabetes (OR 0.91, 95% CI 0.78–1.05). SMI was independently associated with osteoporosis in prediabetes adults (OR 0.65, 95% CI 0.50–0.85). Both sarcopenia and osteoporosis were positively associated with spine fracture in prediabetes (OR 4.48, 95% CI 1.84–10.89, and OR 2.85, 95% CI 1.81–4.47, respectively). The risk of spine fracture was substantially higher in the presence of osteosarcopenia (OR 12.91; 95% CI, 2.68–62.09) than in the presence of sarcopenia or osteoporosis alone in prediabetes. Conclusion In adults with prediabetes, both sarcopenia and osteoporosis are risk factors for spine fracture, and the combination of sarcopenia and osteoporosis further increases the risk of spine fracture.